GE_GERICHTE A/3437/2023 vom 10. April 2024 - GE Cour de justice (2024)
PERMIS DE CIRCULATION;RETRAIT DE PERMIS;EXCÈS DE VITESSE;PROFESSION;POUVOIR D'APPRÉCIATION | LCR.16c.al1.leta; LCR.16c.al2.leta; LCR.90.al2; OAC.33.al5